Expression of both Arabidopsis γ-tubulin genes is essential for development of a functional syncytium induced by Heterodera schachtii - Różańska, Elżbieta (Plant Cell Rep, 2018)
KEY MESSAGE: After initial up-regulation, expression of TUBG1 and TUBG2 is significantly down-regulated in mature syncytia, but lack of expression of either of γ-tubulin genes reduces numbers of nematode infections and developing females. ABSTRACT: Infective second stage juveniles of sedentary plant parasitic nematode Heterodera schachtii invade the root vascular tissue and induce a feeding site, named syncytium, formed as a result of cell hypertrophy and partial cell wall dissolution leading to a multinucleate state. Syncytium formation and maintenance involves a molecular interplay between the plant host and the developing juveniles leading to rearrangements and fragmentation of the plant cytoskeleton. In this study, we investigated the role of two Arabidopsis γ-tubulin genes (TUBG1 and TUBG2), involved in MTs nucleation during syncytium development. Expression analysis revealed that both γ-tubulin’s transcript levels changed during syncytium development and after initial up-regulation (1–3 dpi) they were significantly down-regulated in 7, 10 and 15 dpi syncytia. Moreover, TUBG1 and TUBG2 showed distinct immunolocalization patterns in uninfected roots and syncytia. Although no severe changes in syncytium anatomy and ultrastructure in tubg1-1 and tubg2-1 mutants were observed compared to syncytia induced in wild-type plants, nematode infection assays revealed reduced numbers of infecting juveniles and developed female nematodes in mutant lines. Our results indicate that the expression of both TUBG1 and TUBG2 genes, although generally down-regulated in mature syncytia, is essential for successful root infection, development of functional syncytium and nematode maturation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00299-018-2312-7) contains supplementary material, which is available to authorized users.